MRPS25 mutations impair mitochondrial translation and cause encephalomyopathy - Bugiardini, Enrico (Hum Mol Genet, 2019)
Mitochondrial disorders are clinically and genetically heterogeneous and are associated with a variety of disease mechanisms. Defects of mitochondrial protein synthesis account for the largest subgroup of disorders manifesting with impaired respiratory chain capacity; yet, only a few have been linked to dysfunction in the protein components of the mitochondrial ribosomes. Here, we report a subject presenting with dyskinetic cerebral palsy and partial agenesis of the corpus callosum, while histochemical and biochemical analyses of skeletal muscle revealed signs of mitochondrial myopathy. Using exome sequencing, we identified a homozygous variant c.215C>T in MRPS25, which encodes for a structural component of the 28S small subunit of the mitochondrial ribosome (mS25). The variant segregated with the disease and substitutes a highly conserved proline residue with leucine (p.P72L) that, based on the high-resolution structure of the 28S ribosome, is predicted to compromise inter-protein contacts and destabilize the small subunit. Concordant with the in silico analysis, patient’s fibroblasts showed decreased levels of MRPS25 and other components of the 28S subunit. Moreover, assembled 28S subunits were scarce in the fibroblasts with mutant mS25 leading to impaired mitochondrial translation and decreased levels of multiple respiratory chain subunits. Crucially, these abnormalities were rescued by transgenic expression of wild-type MRPS25 in the mutant fibroblasts. Collectively, our data demonstrate the pathogenicity of the p.P72L variant and identify MRPS25 mutations as a new cause of mitochondrial translation defect.